Meta analisis: Efektivitas terapi Applied Behavior Analysis terhadap kemampuan komunikasi anak dengan Autism Spectrum Disorder - Chandrawijaya, Elvina Febriyani (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2021)
Many children with Autism Spectrum Disorder (ASD) become frustrated in their attempts to make their feelings, thoughts, and needs known. They may act out their frustrations through inappropriate behaviors. This lack of communication skill needs to be treated early to prevent future developmental delays. Applied Behavior Analysis (ABA) is the most frequently used intervention for children with Autism Spectrum Disorder (ASD). However, many studies have found inconsistent results regarding its effectiveness. This study aims to determine the effectiveness of ABA on the communication skills of children with ASD assessed by Vineland Adaptive Behavior Scales (VABS). Meta analysis method is used in this study. Data is processed through statdirect trial version 3.0 application. This study involved 14 experiments using ABA therapy for children with ASD (total n experiment groups = 304 and total n control groups = 244). Based M, SD, and N on data analysis, the effect size value obtained from the fixed effect (I² = 55.7%) was 0.210 (95% CI = 0.035 to 0.384; small effect size). These results do not support the effectiveness of ABA in improving communication skills in ASD children. We suggests that ABA therapy should be carried out with other interventions that target specific communication skills. Future researchers should conduct research replication to increase references on the effectiveness of ABA therapy.